Analyzing esophageal squamous cell papillomas for the presence of human papilloma virus - Arzu Tiftikçi,; Eser Kutsal,; Ender Altıok,; Ümit İnce,; Bahattin Çicek,; Murat Saruç,; Nurten Türkel,; Özdal Ersoy,; Güven Yenmiş,; Nurdan Tözün, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Human Papilloma Virus (HPV) infection can be a predisposing condition for the development of squamous cell papilloma (SCP) of the esophagus, which can progress to dysplasia and to carcinoma as a result of chronic infection. The aim of the present study was to search for the presence of HPV in the esophageal SCP, and to genotype the detected HPV. Materials and Methods: Data from patients with definite diagnosis of SCP of the esophagus were identified from pathology records for two years period at different Hospitals. Slides from each patient were reviewed and samples with satisfactory papilloma tissues were submitted to molecular analysis. DNA has been isolated. DNA sequencing has been performed for genotyping HPV for all types. Results: Our study group consisted of 21 women and 17 men (a total of 38 patients), mean age was 41 years (range 17-67 years). Most of the papillomas were located at mid-esophagus (68%). Eight out of 38 patients (21%) had associated erosive esophagitis, and fourteen patients (36.8%) had Helicobacter Pylori (H. pylori). Of the 38 SCP analyzed, seven (19%) were positive for HPV DNA. Three of them were of genotype 6, whereas four were of genotype 16,18,31,81 that are known as highly oncogenic. There were no correlations between the presence of HPV and the patient’s age, the presence of reflux esophagitis or H. pylori, smoking habit and the location of the papillomas. Conclusion: The presence of high-risk type HPV in esophageal SCP may implicate a role of the virus in the pathogenesis of the esophageal tumor.